ABORTIFACIENT EFFICACY OF INDIGOFERA TRIFOLIATA LEAVES EXTRACT ON FEMALE ALBINO RATS - DABHADKAR DINESH; Varsha, Zade (Asian Journal of Pharmaceutical and Clinical Research, 2013)
To evaluate the potential abortifacient activity of the aqueous, alcohol, ethyl acetate and chloroform extract of Indigofera trifoliata leaves in female albino rats 100, 200 and 400 mg/kg body weight doses of each extract were administered from day 11 to 15 of pregnancy and animals were allowed to go full term. The phytochemical screening revealed the presence of alkaloids, flavonoids, simple phenolics, steroids, tannins and saponins. Clinical toxicity symptoms such as respiratory distress, salivation, weight loss, dull eyes, diarrhea, and change in the appearance of fur as well as mortality were not observed in the animals at any period of the experiment. All the four extracts of I. trifoliata leaves exhibited abortifacient activity (7- 92.30%). The extracts significantly reduced the number of live fetuses, whereas the resorption index and post implantation losses increased significantly. The % of abortion was found to be highest (92.30%) with 400 mg/kg dose of alcoholic extract of I. trifoliata leaves. The hormonal assay shows that, there was reduction in the level of FSH and LH hormone, while level of estrogen increased but there was slight decrease in the level of progesterone hormone. The extract shows significant change in the body weight but there was slight decrease in weight of ovary and increase in the uterine weight in treated rats. Keywords: Abortifacient, Female albino rat, Indigofera trifoliata, Post implantation, Resorption